DAYA SAING CRUDE PALM OIL (CPO) INDONESIA DAN MALAYSIA DI LIMAPASAR UTAMA TAHUN 2001 – 2018 - Ginanjar Sastro Sasmito; Lorentino Togar Laut; Rian Destiningsih (DINAMIC : Directory Journal of Economic, 2020)
International trade is a "growth engine" for a country. In international trade, a country must has an advantage in a product that being traded. CPO is one of Indonesia'sexport commodities which have a lot of economic potentials to increase state incomes.Indonesia is the largest CPO exporter in the world by fulfill the world's CPO needs in ±54%, followed by Malaysia in ± 28%. India, Netherlands, Spain, Kenya and Italy thatcalled the countries with the largest CPO importers in the world. The purpose of this studyis to analyze the competitive position of CPO commodities between Indonesia andMalaysia in five main markets in the periods between 2001 - 2018. The analysis tools thatbeing used are RCA (Revealed Comparative Advantage), EPD (Export Product Dynamic),and ISP (Trade Specialization Index). The RCA calculation result shows that Indonesia and Malaysia have strong competitiveness in the five main markets (India, Netherland, Spain, Kenya, and Italy), but Indonesia only loses its superiority in Spain. The EPD calculation result shows that Indonesia includes in the rising star classification in the countries of India and Kenya. ISP calculation result shows that Indonesia and Malaysia are net CPO exporters countries and Indonesia stays at the maturity stage while Malaysia stays at the growth stage and re-import stage.